Demand Constraints and Economic Growth - Marc-Andre Pigeon; L. Randall Wray (Levy Economics Institute of Bard College, 1999)
In recent years the U.S. has seemed to achieve the best of all possible worlds: robust economic growth, very low unemployment, and low inflation. Many attribute this performance to fewer supply side constraints, as the U.S. has moved away from stifling regulations and other impediments to trade. When compared with the very high unemployment rates suffered in European countries, our lower unemployment rates appear to be due to freer labor markets and to a less generous social safety net that saps private initiative. In this paper we show that although it is true the U.S. has enjoyed a higher employment rate than all of our major competitors, we lag behind all other major countries in per capita GDP growth since 1970. The reason is our dismal rate of productivity growth. We show that when one decomposes per capita GDP growth into its component parts–growth of employment rates and growth of output per employee–the U.S. experience is quite different from that of the other countries. In some sense, countries "choose" high employment paths or low employment paths, but regardless of that choice, economic growth does not appear to be much affected. We argue that this is because countries have not faced significant supply constraints; rather, per capita GDP growth has been largely demand constrained. For this reason policies aimed at removing supply constraints do not lead to more rapid economic growth. The conclusion is that, if one is to trying to increase growth rates, Keynesian "demand side" policies are preferable to "supply side" policies.
Keywords: 330